Family business groups and earnings manipulation: An emerging economy perspective - Sattar Khan; Yasir Kamal (Cogent Economics & Finance, 2022)
This paper examines the influence of family business groups' affiliated and non-affiliated firms on earnings manipulation on a sample of Pakistani listed firms for the period of 2014 to 2019. The sample of this paper consists of 323 listed firms from the Pakistan Stock Exchange. Data were manually collected from the annual reports of the companies and State Bank of Pakistan sources. OLS and The Panel data models are used to validate the hypotheses of the study. Two proxies of earnings management have been used: one is discretionary accruals and the other is real activity manipulation. The study findings show a negative relationship of family business groups' affiliated firms with accrual-based earnings manipulation. Additionally, the magnitude of earnings manipulation is more in non-affiliated firms as compared to family business group affiliated firms. This study provides rare and initial evidence of family business groups' relationship with earnings manipulation in Pakistan; moreover, this study extends the literature on scarce literature related to Family business groups and earnings manipulation.
Keywords: G30; G32; G11; 330; Earnings manipulation; family business groups; corporate governance; Pakistan Stock Exchange